2022
DOI: 10.1096/fj.202101521r
|View full text |Cite
|
Sign up to set email alerts
|

The collectrin‐like part of theSARS‐CoV‐1 and ‐2receptorACE2is shed by the metalloproteinasesADAM10andADAM17

Abstract: The transmembrane protease angiotensin converting enzyme 2 (ACE2) is a protective regulator within the renin angiotensin system and additionally represents the cellular receptor for SARS‐CoV. The release of soluble ACE2 (sACE2) from the cell surface is hence believed to be a crucial part of its (patho)physiological functions, as both, ACE2 protease activity and SARS‐CoV binding ability, are transferred from the cell membrane to body fluids. Yet, the molecular sources of sACE2 are still not completely investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…(Adrain et al 2012, Blaydon et al 2012, McIlwain et al 2012, Christova et al 2013. Furthermore, strategies targeting iRhom functions to modulate ADAM17 activity and cell surface localisation may have beneficial implications for the prevention and treatment of viral diseases in humans and cattle due to the role of ADAM17 in SARS-CoV1/2 and pestivirus infections, respectively (Lambert et al 2005, Heurich et al 2014, Hoffmann et al 2020, Yuan et al 2021, Jocher et al 2022, Niehues et al 2022, Zaruba et al 2022. Finally, beyond the proinflammatory signalling and virus infections, dysregulated ADAM17 is involved in cancer progression through proteolytic release of EGF receptor ligands (Bender et al 2016, Moss et al 2017, Düsterhöft et al 2019b, Saha et al 2022.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Adrain et al 2012, Blaydon et al 2012, McIlwain et al 2012, Christova et al 2013. Furthermore, strategies targeting iRhom functions to modulate ADAM17 activity and cell surface localisation may have beneficial implications for the prevention and treatment of viral diseases in humans and cattle due to the role of ADAM17 in SARS-CoV1/2 and pestivirus infections, respectively (Lambert et al 2005, Heurich et al 2014, Hoffmann et al 2020, Yuan et al 2021, Jocher et al 2022, Niehues et al 2022, Zaruba et al 2022. Finally, beyond the proinflammatory signalling and virus infections, dysregulated ADAM17 is involved in cancer progression through proteolytic release of EGF receptor ligands (Bender et al 2016, Moss et al 2017, Düsterhöft et al 2019b, Saha et al 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ADAM17s diverse role in virus cell entry was discovered. ADAM17 can cleave the SARS-CoV-1/2 (severe acute respiratory syndrome coronavirus 1/2) receptor ACE2 and the SARS-CoV2 spike, which is an important requisite for efficient infections (Lambert et al 2005, Heurich et al 2014, Hoffmann et al 2020, Jocher et al 2022, Niehues et al 2022. Furthermore, ADAM17 was identified as the entry factor of pestiviruses in cattle (Yuan et al 2021, Zaruba et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al also reported significant increases in soluble (s)ACE2 concentrations in cultures of human bronchial epithelial cells treated with OM-85 for 4-5 days [ 36 ]. Interestingly, OM-85 also upregulated expression of a disintegrin and metalloprotease 17 (ADAM17) ] which was implicated in sACE2 shedding [ 42 , 43 ]. While the role of sACE2 in the pathophysiology of SARS-CoV-2 infection is unclear, increased ACE2 shedding may contribute to OM-85-mediated inhibition of SARSCoV- 2 infection by decreasing the availability of membrane ACE2.…”
Section: Where We Are…mentioning
confidence: 99%
“…However, the MAS receptor, encoded by MAS1, acts in the opposite way by binding to angiotensin 1-7, a peptide derived from the breakdown of angiotensin I by ACE2. This binding activates signaling pathways that cause vasodilation, reduce blood pressure, and exert antiin ammatory and anti brotic effects (Abdel Ghafar ADAM17, a metalloproteinase involved in the shedding of cell surface proteins including ACE2, has also drawn interest due to its potential interplay with the RAS and the immune response during viral infections, including COVID-19 (Niehues et al 2022). Furthermore, emerging studies have indicated the involvement of SOX3 (SRY-Box Transcription Factor 3) in the regulation of ACE2 expression.…”
Section: Introductionmentioning
confidence: 99%